2014
DOI: 10.1039/c3dt53305k
|View full text |Cite
|
Sign up to set email alerts
|

Probing the highly efficient room temperature ammonia gas sensing properties of a luminescent ZnO nanowire array prepared via an AAO-assisted template route

Abstract: Here, we report the facile synthesis of a highly ordered luminescent ZnO nanowire array using a low temperature anodic aluminium oxide (AAO) template route which can be economically produced in large scale quantity. The as-synthesized nanowires have diameters ranging from 60 to 70 nm and length ∼11 µm. The photoluminescence spectrum reveals that the AAO/ZnO assembly has a strong green emission peak at 490 nm upon excitation at a wavelength of 406 nm. Furthermore, the ZnO nanowire array-based gas sensor has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 56 publications
(68 reference statements)
1
23
0
Order By: Relevance
“…The sensitization mechanism for most of the semiconducting metal oxides works on the principle of changing the conductivity of the sensor materials due to the interaction between the gas and the oxygen ions adsorbed on the surface ( -O 2 , O -, O 2-), which appears when the sensor is exposed to atmospheric oxygen. This leads to the formation of an area of depletion as a result of extracting electrons from the conduction band, thus increasing the barrier of sensor and thereby increasing the sensor resistance [18]. When the sensor is exposed to ammonia gas (NH 3 ), the gas reacts with oxygen ions and the electrons are released to the conduction band, which leads to a decrease in the electrical resistance of the sensor, according to the following equations [19]:…”
Section: -3 Gas Sensor Characteristicsmentioning
confidence: 99%
“…The sensitization mechanism for most of the semiconducting metal oxides works on the principle of changing the conductivity of the sensor materials due to the interaction between the gas and the oxygen ions adsorbed on the surface ( -O 2 , O -, O 2-), which appears when the sensor is exposed to atmospheric oxygen. This leads to the formation of an area of depletion as a result of extracting electrons from the conduction band, thus increasing the barrier of sensor and thereby increasing the sensor resistance [18]. When the sensor is exposed to ammonia gas (NH 3 ), the gas reacts with oxygen ions and the electrons are released to the conduction band, which leads to a decrease in the electrical resistance of the sensor, according to the following equations [19]:…”
Section: -3 Gas Sensor Characteristicsmentioning
confidence: 99%
“…When the SnO 2 is exposed to air at room temperature, oxygen molecules on the surface capture electrons 90 from the conduction band of SnO 2 , and electrons divert from the oxygen vacancies of SnO 2 to the oxygen molecule form more chemisorbed oxygen species O 2 in the surface. [68][69][70] The reactions of eqs 1-3 take place on the surface of SnO 2 as follows: (3) wherein V O is oxygen vacancy, and V O · · · · is single electropositive oxygen vacancy. It has been reported that higher oxygen vacancy density would induce more surface absorbed oxygen species.…”
Section: Sensing Mechanismmentioning
confidence: 99%
“…Increasing the concentration of ammonia in air causes severe adverse effects in the human respiratory system, eyes and skin. Over the past decade, several techniques for the detection of NH3have been reported based on measurements of electrical current in nano structured metal oxides [3], conducting polymers [4], carbon nanotubes [5] and nano structured graphene [6].Optical fiber based sensors have some unique advantages over their electrical analogues such as remote and real time monitoring, immunity to various sources of disturbance such as electromagnetic interference, radioactivity, and explosive environments. Amongst the optical fiber techniques, sensors based on the whispering gallery modes (WGMs) in spherical microresonators have found many applications in the fields of molecular adsorption [7],refractive index [8],temperature [8] and gas sensing [9] due to their ultra-high quality factors, low absorption losses and inexpensive fabrication.…”
Section: Introductionmentioning
confidence: 99%